Mycorrhizal Fungi Fortification: Healthy PlantingMaterial Production in Black Pepper - Sarathambal, C; Kandiannan , K; Srinivasan, V (Indian Horticulture, 2024)
Research affirms that Arbuscular mycorrhizae play a crucial role in mobilizing essential soil nutrients such as phosphorus, nitrogen, zinc, iron, calcium, magnesium, manganese, sulphur, etc. They achieve this by enzymatically releasing these nutrients from tightly held chemical bonds and transporting them back to the plant. Additionally, mycorrhizae have been acknowledged for enhancing plant disease resistance, improving its ability to thrive under drought conditions, and enhancing soil structure. The paper discusses its beneficial app lications in nursery condition on black pepper.